Preparation method, characterization method and application of mu-DIC speckles of magnesium alloy

By using electrolytic polishing and ultrasonic treatment on magnesium alloy materials, uniform speckle particles with particle size of 20~60nm were prepared, which solved the problem of difficulty in combining EBSD and HR-DIC technology on magnesium alloy materials, and achieved efficient material characterization.

CN119555463APending Publication Date: 2025-03-04ANHUI UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411825289.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, it is difficult to achieve an effective combination of EBSD and HR-DIC technology on magnesium alloy materials, and the speckle preparation method has problems such as complex operation, long cycle and high cost, which cannot meet the EBSD testing needs.

Method used

The magnesium alloy sample was treated with a small current density and long-term electropolishing method, and combined with the ultrasonic treatment of SiO2 suspension and anhydrous ethanol, uniformly dispersed and distributed speckle particles with a particle size of 20~60nm were prepared.

Benefits of technology

NanoSiO2 speckle uniformly distributed on the surface of magnesium alloy is achieved, which avoids the damage and oxidation of the sample surface, ensures the clarity of the EBSD signal, and realizes the effective combination of EBSD and HR-DIC technology, improving the material characterization efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119555463A_ABST
    Figure CN119555463A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a magnesium alloy mu-DIC speckle and a characterization method and application thereof. The preparation method comprises the following steps: 1) carrying out electrolytic polishing on a to-be-detected surface of a magnesium alloy sample until the to-be-detected surface is bright and free of scratches; 2) mixing the SiO2 suspension with alcohol according to a certain volume ratio, and performing ultrasonic dispersion to obtain a diluent; 3) placing the polished sample in a diluent for ultrasonic treatment, and then cleaning the sample with alcohol to obtain uniformly dispersed and distributed speckles; the whole preparation of the speckles is a physical process, the sample is not damaged or the properties of the sample are not changed, and the speckles prepared by the method do not interfere with the collection of other signals on the surface of the sample, so that the practicability of EBSD and DIC results is improved; the preparation method has the advantages of being simple, easy to operate, efficient, ultralow in cost and the like, the magnesium alloy material can be applied under the room temperature, high resolution and large view field, and the bottleneck problems that the magnesium alloy sample speckle preparation difficulty is large, and compatibility of the DIC technology and the EBSD technology cannot be achieved at the same time are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of optical measurement mechanics and deformation measurement technology, and relates to a method for preparing μ-DIC speckles of magnesium alloys, a method for characterizing the same and applications thereof, and in particular to a method for preparing speckles for high-resolution local strain analysis of magnesium alloy materials, a method for characterizing local strains in micro-areas on the surface and applications thereof. Background Art

[0002] Digital imaging technology (DIC) is an experimental testing technology that combines modern digital image processing and analysis technology. Different from the one-dimensional data of traditional mechanical measurements, this non-contact optical strain measurement system can intuitively and clearly reflect the two-dimensional or even three-dimensional deformation behavior of the measured object. This technology does not require a special measurement environment and has a very wide measurement range and powerful extended analysis capabilities. Introducing it into the mechanical properties test of materials can make detailed observations and analyses of the microscopic strain evolution of materials, which helps to more deeply understand the damage mechanism and deformation behavior of materials from a microscopic or even smaller scale.

[0003] Combining electron backscatter diffraction (EBSD) with the DIC phase method can achieve strain measurement at the microscopic scale of metal materials, which can be used to study the deformation mechanism of metal materials. Due to the significant anisotropy of the constituent phases and different grains of metal materials, there are complex local deformations and strain coordination during the deformation process. It is particularly suitable to use EBSD and high-resolution DIC (HR-DIC) methods to study deformation mechanisms at different scales. Combining EBSD and HR-DIC technology to characterize and analyze the local strain distribution and evolution process of the material during deformation, combined with microstructure and deformation substructure analysis, helps to deeply understand the microscopic mechanism of deformation coordination and damage failure.

[0004] The size and quality of the speckle used in HR-DIC strain analysis of magnesium alloys directly determine the resolution and accuracy of strain measurement. Although several speckle preparation methods for metal materials have been proposed at this stage, it is difficult to achieve an effective combination of EBSD and HR-DIC technology on magnesium alloys due to the fact that magnesium alloys are extremely susceptible to corrosion and oxidation.

[0005] For example, a Chinese invention patent (publication number: CN114609168A) discloses a DIC speckle preparation method and a method for characterizing local strain in a micro-area of ​​a metal material. This method uses an electron beam system to bombard the sample surface to obtain speckles. This method not only damages the sample surface and affects the analysis of EBSD, but also has a high production cost and is difficult to promote and use. A Chinese invention patent (publication number: CN114608949A) discloses a test method for the mechanical properties of a rare earth magnesium alloy after corrosion and its application. This method first sprays a layer of white paint evenly on the sample surface, waits for the white paint to completely dry, and then sprays black paint on the surface to form uniform and random speckles. First, the speckle particles formed by this method are large and sparse, which is not suitable for microscopic DIC analysis on SEM. Secondly, the sample surface is damaged after spraying, and EBSD analysis cannot be performed, making it difficult to combine EBSD and DIC technology. A Chinese patent (publication number: CN110487831A) discloses a method for preparing speckle and a method and device for preparing nano-gold particle coating speckle, wherein a metal film is attached to the surface of the sample and heated in a steam atmosphere to obtain nano-particle coating speckle. However, the speckle preparation technology requires the sample to be heated for a long time at 200-300°C in a steam atmosphere. For magnesium alloys, long-term heating treatment causes changes inside the sample, and the surface of the magnesium alloy sample is prone to oxidation in a steam environment. In addition, due to the low atomic number of magnesium alloys, the metal nano-particle coating speckle will block the EBSD signal and affect the EBSD analysis of magnesium alloys. This method can only obtain EBSD information for magnesium alloy samples before deformation, and cannot perform EBSD analysis on samples after speckle treatment, and cannot achieve the combination of EBSD and DIC technology. A Chinese invention patent (publication number: CN111610210A) discloses a SEM-DIC speckle preparation method for characterizing the local strain distribution characteristics of materials. The method uses KOH, 40% silica sol, polyhydroxy polymer and distilled water to mix and ultrasonically disperse to obtain a SiO2 suspension, and then drips the suspension onto the sample surface to spread freely, then uses filter paper to absorb the surface droplets from the edge of the droplet, then slowly tilts the sample surface, rinses it with anhydrous ethanol, and finally quickly dries it to obtain uniform speckles. Since magnesium alloys are very easy to oxidize, this method causes the surface of the magnesium alloy sample to turn black, and the resulting SiO2 particles to agglomerate severely. In addition, the drip method used in this patent is often random, which fully tests the operating experience of the preparation personnel. In summary, among the existing methods for preparing speckles, some process operations are complex, the cycle is long, the production cost is high, and they cannot meet the EBSD test requirements and cannot achieve the combination of EBSD and DIC technology.

[0006] The inventor of this application, through studying his own subject and in the long-term experimental process, invented a method combining SEM, EBSD and DIC techniques on magnesium alloy materials. This method not only realizes multiple characterization methods through in-situ deformation experiments, but also has low cost and is easy to operate. Most of the existing speckle preparation technologies are too complicated to operate, and have high costs, long experimental cycles, or are incompatible with EBSD technology. In summary, the key issue lies in the preparation of speckles and the combination of multiple characterization techniques. Summary of the invention

[0007] In view of this, the present invention provides a method for preparing μ-DIC speckle of magnesium alloy and a characterization method and application thereof, in order to solve the problems that the existing method for preparing speckle is applicable to magnesium alloy materials, the above-mentioned process operation is complex, the cycle is long, the production cost is high, the EBSD test requirements cannot be met, and the preparation of speckle and multiple characterization technologies cannot be combined with each other. The technical problems of low speckle resolution, surface damage and inability to achieve compatibility between EBSD and HR-DIC technologies in the prior art are solved.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] A method for preparing μ-DIC speckle of magnesium alloy comprises the following steps:

[0010] S1. Electrolytic polishing of magnesium alloy samples was performed using a low current density and long-time electrolytic polishing method;

[0011] S2, mixing the SiO2 suspension having a pH value of 8-11 with anhydrous ethanol in a volume ratio of 1:100-2000 and performing ultrasonic treatment to obtain a nano-SiO2 dilution solution;

[0012] S3. The magnesium alloy sample after electrolytic polishing in step S1 is placed in the SiO2 diluted solution treated in step S2 for ultrasonic treatment. Then the magnesium alloy sample is taken out, cleaned with alcohol and blown dry to form uniformly dispersed speckle particles on the surface of the magnesium alloy sample. The particle size of the speckle SiO2 is 20-60 nm.

[0013] The beneficial effects of this basic scheme: The use of low current density and long-term electrolytic polishing can obtain a clean and flat surface of the magnesium alloy sample to be tested, which is conducive to the adsorption of nanoparticles on the surface of the magnesium alloy sample by physical adsorption to obtain uniformly dispersed speckle particles. Too much current density will cause convexity on the sample surface, which is not conducive to the uniform attachment of speckle particles to the sample surface, resulting in agglomeration or too sparse distribution of speckle particles on the sample surface. If the current density is too small, it will make it difficult to remove the stress layer on the sample surface, resulting in a significant reduction in the EBSD recognition rate or even inability to perform EBSD characterization analysis.

[0014] When the concentration of SiO2 suspension is too high, the concentration of SiO2 particles in the diluent is too high, so that too many speckle particles are adsorbed on the sample surface, which is prone to agglomeration and interference with EBSD signals; on the contrary, when the concentration of SiO2 suspension is too low, the concentration of SiO2 particles in the diluent is too low, and the number of speckles adsorbed on the sample surface is limited, affecting the accuracy of DIC measurement. Preferably, the volume ratio of SiO2 suspension to anhydrous ethanol is 1:100~2000. Compared with water and other volatile organic solvents, anhydrous ethanol has the advantages of being cheap, easy to obtain, non-toxic, and volatile, and will not damage or oxidize the surface of magnesium alloy samples, and can effectively weaken the destructiveness of SiO2 suspension on the surface of magnesium alloy samples.

[0015] If the particle size of the speckle SiO2 is too high, it may interfere with the EBSD signal. If the particle size is too low, the speckle particles are prone to agglomeration, affecting the DIC resolution. When the particle size of the speckle SiO2 is 20-60nm, the dispersion effect of the suspension is good and it will hardly interfere with the EBSD signal.

[0016] Further, step S1 is specifically as follows: the magnesium alloy sample is polished from coarse to fine on 600#, 800#, 1000#, 1600#, 2000#, and 3000# sandpaper in sequence until the surface is in a mirror state, and then the magnesium alloy sample is electropolished using ACII electrolyte, the electropolishing voltage is 20V, the polishing temperature is -15~-30℃, the current density is controlled at 30~60mA, and the polishing time is 60~150s to obtain a magnesium alloy sample with a smooth surface and no stress.

[0017] Furthermore, in step S2, an ultrasonic cleaning machine is used to ultrasonically disperse the dilution solution so that the SiO2 particles can be evenly dispersed in the solution without agglomeration. The ultrasonic power is 50-150W, the ultrasonic time is 30-80min, and the ultrasonic temperature is 20-50°C. If the ultrasonic time is too short, the particles cannot be evenly dispersed, and if the ultrasonic time is too long, the efficiency is low. If the ultrasonic temperature is too low, the nanoparticles are prone to agglomeration, and if the ultrasonic temperature is too high, the nanoparticles are destroyed.

[0018] Furthermore, in step S3, the ultrasonic power is 50-150 W, the ultrasonic time is 5-30 min, and the ultrasonic temperature is 20-50° C.

[0019] Ultrasonic treatment can make the speckle particles in the dilution solution evenly adhere to the surface of the magnesium alloy sample by physical adsorption effect. Under the action of ultrasound, the speckle particles are evenly dispersed and adsorbed on the surface of the magnesium alloy sample without agglomeration. If the ultrasonic time is too short, the nanoparticles will stack and agglomerate on the surface of the sample. If the ultrasonic time is too long, the speckle particles on the surface of the sample will be sparse, reducing the resolution of DIC.

[0020] The method for characterizing local strain in micro-regions on the surface of a magnesium alloy comprises the following steps:

[0021] S1, using the above-mentioned magnesium alloy μ-DIC speckle preparation method to prepare speckles on the surface of the magnesium alloy sample;

[0022] S2, photographing the magnesium alloy sample with speckles prepared in step S1 by using a secondary electron imaging mode of a scanning electron microscope to obtain a scanning electron microscope photograph (SEM image) of an undeformed morphology, and photographing the region by using a backscattered electron diffraction mode to obtain an EBSD image of the region without deformation;

[0023] S3, performing a deformation operation on the magnesium alloy sample, photographing the deformed magnesium alloy sample through a secondary electron imaging mode of a scanning electron microscope after the magnesium alloy sample is deformed to obtain a SEM image after deformation, and photographing the region in a backscattered electron diffraction mode to obtain an EBSD image of the region after deformation;

[0024] S4. Compare and analyze the undeformed SEM image in step S2 and the deformed SEM image in step S3 using computer software to obtain displacement and local strain information, and characterize the local strain of the magnesium alloy sample.

[0025] Furthermore, the deformation in step S3 includes bending, stretching or compression.

[0026] Further, step S4 is specifically as follows: using EBSD data to obtain a grain boundary distribution map of the magnesium alloy sample material, and then obtaining a local strain distribution of the magnesium alloy sample based on the speckles on the undeformed SEM image and the deformed SEM image; overlapping the grain boundary distribution map with the local strain distribution to obtain a cloud map containing both grain boundary information and strain distribution.

[0027] The above-mentioned application of the local strain characterization method of the micro-area on the surface of magnesium alloy is used for the evaluation of the plastic deformation mechanism and damage failure of magnesium alloy, the optimization of magnesium alloy processing technology, the prediction of the service life of magnesium alloy, etc.

[0028] The beneficial effects of the present invention are:

[0029] 1. The method for preparing μ-DIC speckle of magnesium alloy disclosed in the present invention uses physical adsorption to make speckle particles uniformly and dispersedly adsorbed on the surface of magnesium alloy sample, and the whole process will not pollute and damage the surface of magnesium alloy sample to be tested. SiO2 suspension is diluted with anhydrous ethanol at a high volume ratio, and fully dispersed by ultrasound, so that SiO2 particles can be uniformly dispersed without agglomeration. In addition, ACII solution is used to electropolish the magnesium alloy for a long time and at a low current density, so that the surface of the sample is flat, and SiO2 particles can be uniformly and dispersedly adsorbed on the surface of magnesium alloy sample. The electropolished magnesium alloy sample is placed in the diluted and dispersed SiO2 solution, and then ultrasonically dispersed, so that SiO2 particles are uniformly and dispersedly adsorbed on the surface of magnesium alloy sample by physical adsorption effect. After high volume ratio dilution, the surface of magnesium alloy will not be damaged by the addition of SiO2 suspension, causing the surface to be blackened or oxidized. In addition, speckle particles can be uniformly and dispersedly distributed on the surface of the sample with appropriate thickness, so that these speckle particles will not interfere with the collection of EBSD signals. The speckle particles are nano-sized and have a large specific surface area, so they can be effectively adsorbed on the sample surface. After a certain period of ultrasonic treatment, the speckle is not easy to fall off during the sample loading and deformation process. Therefore, the EBSD test can be performed on the sample surface while the DIC experiment is being performed, which significantly improves the characterization efficiency of the material and realizes the effective combination of EBSD and HRDIC technology. It can be seen that the speckle preparation method of the present invention has the advantages of simple process, strong practicality, short time and low cost.

[0030] 2. Compared with the method of reshaping nanoparticle gold, the method for preparing μ-DIC speckle of magnesium alloy disclosed in the present invention has low cost, high efficiency, does not block EBSD signals, and can achieve effective compatibility between EBSD and HR-DIC technology. Compared with the method of dripping, rotating pressing or spraying with a spray gun for SiO2 suspension, the method adopted by the present invention is more efficient, has better uniformity, is simple to operate, is not affected by operator experience, and has better prepared speckle effect, which is conducive to improving the accuracy, reliability and precision of the test results. In addition, the HR-DIC speckle preparation method provided by the present invention is simple to operate, low cost, high efficiency, and is not affected by factors such as operator experience.

[0031] 3. The method for preparing μ-DIC speckle of magnesium alloy disclosed in the present invention controls the particle size of SiO2 speckle particles to be 20-60nm. The speckle particles still have excellent characteristics when magnified to 5000 to 50000 times, and the nanometer-level particle size ensures the accuracy of DIC analysis, improves the resolution of DIC data, and meets the analysis of global domain strain and local high-precision strain DIC data in the experimental process. This method can not only be used to study the microscopic deformation mechanism of magnesium alloy materials, expand the research scope from microstructure to grain, but also provide a micro-nanometer-level speckle preparation idea for other fields that need to use DIC technology for analysis.

[0032] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0034] Figure 1 This is a SEM photo of the speckle of the original sample of Example 1 of the present invention;

[0035] Figure 2 This is the EBSD image of the original sample (including speckles) of Example 1 of the present invention;

[0036] Figure 3 This is a SEM photograph of speckles of the sample of Example 2 of the present invention after being stretched and deformed by 3%;

[0037] Figure 4 It is a superposition diagram of the grain boundary map and the strain field map obtained after the sample of Example 2 of the present invention is stretched and deformed by 3%;

[0038] Figure 5 This is a SEM photo of the speckle of the original sample of Example 3 of the present invention;

[0039] Figure 6 This is the EBSD image of the sample of Example 4 of the present invention after being stretched and deformed by 3.5%. DETAILED DESCRIPTION

[0040] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0041] The present invention provides a method for preparing μ-DIC speckles of magnesium alloys, and the sample can be a magnesium alloy material in a cast state, a solid solution state, a deformed state, an aged state, etc. The following takes the preparation of speckle particles on the surface of a deformed magnesium alloy sample as an example to illustrate the detailed preparation process of the present invention.

[0042] Embodiment 1:

[0043] S1. Use wire cutting to cut the gauge section size to 1*2.4*5mm 3 The magnesium alloy in-situ tensile sample was polished with sandpaper of models 600#, 800#, 1000#, 1600#, 2000# and 3000# in sequence, and then the magnesium alloy sample was electropolished with ACII polishing liquid. The electropolishing voltage was 20V. Liquid nitrogen was added to the ACII polishing liquid to make the polishing liquid temperature -20°C. A stainless steel sheet was used as the negative electrode, and the sample was placed in the polishing liquid as the positive electrode. The current density during polishing was 50mA, and the polishing time was 65s. After polishing, the sample surface was cleaned with alcohol.

[0044] S2, mixing a SiO2 suspension having a pH value of 10.2 with anhydrous ethanol in a volume ratio of 1:300 to prepare a desired SiO2 dilution, and performing ultrasonic treatment at 30°C for 75 minutes with an ultrasonic power of 120 W to obtain an ultrasonically diluted SiO2 dilution;

[0045] S3. The polished magnesium alloy sample was placed in a diluted SiO2 solution and subjected to ultrasonic treatment at 40°C for 5 min. The sample was taken out and cleaned with alcohol and then dried. Evenly dispersed speckle particles were formed on the surface of the magnesium alloy sample. The specific SEM morphology image is shown in Figure 2. Figure 1 As shown in the figure, and the EBSD image after the speckle particles are attached is shown in the figure Figure 2 As shown, it can be seen that the speckle attachment does not interfere with the EBSD signal and affect the EBSD signal recognition. The sample still has a high EBSD recognition rate (97%).

[0046] Embodiment 2:

[0047] S1. Use wire cutting to cut the gauge section size to 0.6*1*4mm 3The magnesium alloy in-situ tensile sample was polished with sandpaper of models 600#, 800#, 1000#, 1600#, 2000# and 3000# in sequence, and then the magnesium alloy sample was electropolished with ACII polishing liquid. The electropolishing voltage was 20V. Liquid nitrogen was added to the ACII polishing liquid to make the polishing liquid temperature -23°C. A stainless steel sheet was used as the negative electrode, and the sample was placed in the polishing liquid as the positive electrode. The current density during polishing was 32mA, and the polishing time was 140s. After polishing, the sample surface was cleaned with alcohol.

[0048] S2, mixing the SiO2 suspension with a pH value of 9.3 with anhydrous ethanol in a volume ratio of 1:1200 to prepare the desired SiO2 dilution, and performing ultrasonic treatment at 38°C for 43 minutes with an ultrasonic power of 120W to obtain the ultrasonically diluted SiO2 dilution;

[0049] S3. Put the polished magnesium alloy sample into a diluted SiO2 solution, perform ultrasonic treatment at 28°C for 26 minutes, take it out, clean it with alcohol, and then blow it dry. Evenly dispersed speckle particles can be formed on the surface of the magnesium alloy sample.

[0050] In-situ tensile tests were carried out under a scanning electron microscope, and SEM images were collected before and during deformation. After deformation, the speckle images of the deformation area were processed by software to obtain high-resolution strain distribution results. Figure 3 The SEM photo of the speckle after the sample in Example 2 was stretched by 3% is given, and Figure 4 The superposition diagram of the grain boundary map and the strain field map obtained after the sample in Example 2 was tensile deformed by 3% is given.

[0051] Embodiment three:

[0052] S1. Use wire cutting to cut the gauge section size to 1.2*2*6mm 3 The magnesium alloy in-situ tensile sample was polished with sandpaper of models 600#, 800#, 1000#, 1600#, 2000#, and 3000# in sequence, and then the magnesium alloy sample was electropolished with ACII polishing liquid. The electropolishing voltage was 20V. Liquid nitrogen was added to the ACII polishing liquid to make the polishing liquid temperature -16°C. A stainless steel sheet was used as the negative electrode, and the sample was placed in the polishing liquid as the positive electrode. The current density during polishing was 58mA, and the polishing time was 85s. After polishing, the sample surface was cleaned with alcohol.

[0053] S2, mixing the SiO2 suspension with a pH value of 8.8 with anhydrous ethanol in a volume ratio of 1:1600 to prepare the desired SiO2 dilution, and performing ultrasonic treatment at 45°C for 22 minutes with an ultrasonic power of 120W to obtain the SiO2 dilution after ultrasonic dilution;

[0054] S3. Put the polished magnesium alloy sample into the diluted SiO2 solution, perform ultrasonic treatment at 32℃ for 15min, take it out and clean it with alcohol, then blow it dry. Evenly dispersed speckle particles can be formed on the surface of the magnesium alloy sample, such as Figure 5 shown.

[0055] Embodiment 4:

[0056] S1. Use wire cutting to cut the gauge section size to 0.8*1.8*2mm 3 The magnesium alloy in-situ tensile sample was polished with sandpaper of models 600#, 800#, 1000#, 1600#, 2000#, and 3000# in sequence, and then the magnesium alloy sample was electropolished with ACII polishing liquid. The electropolishing voltage was 20V. Liquid nitrogen was added to the ACII polishing liquid to make the polishing liquid temperature -25°C. A stainless steel sheet was used as the negative electrode, and the sample was placed in the polishing liquid as the positive electrode. The current density during polishing was 53mA, and the polishing time was 64s. After polishing, the sample surface was cleaned with alcohol.

[0057] S2, mixing a SiO2 suspension having a pH value of 10.7 with anhydrous ethanol in a volume ratio of 1:800 to prepare a desired SiO2 dilution, and performing ultrasonic treatment at 28°C for 65 minutes with an ultrasonic power of 120 W to obtain an ultrasonically diluted SiO2 dilution;

[0058] S3. Put the polished magnesium alloy sample into a diluted SiO2 solution, perform ultrasonic treatment at 43°C for 8 minutes, take it out, clean it with alcohol, and then blow it dry. Evenly dispersed speckle particles can be formed on the surface of the magnesium alloy sample.

[0059] In-situ tensile tests were carried out under a scanning electron microscope. SEM images and EBSD data were collected before and after deformation. The speckle images of the deformed area were processed by software to obtain high-resolution strain distribution results. Figure 6 The EBSD image of the sample in Example 4 after being stretched and deformed by 3.5% is given. The sample still has a high EBSD recognition rate, and its recognition rate is 92%.

[0060] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing μ-DIC speckle of magnesium alloy, characterized in that: The following steps are involved: S1. Electrolytic polishing of magnesium alloy samples was performed using a low current density and long-time electrolytic polishing method; S2, mixing the SiO2 suspension having a pH value of 8-11 with anhydrous ethanol in a volume ratio of 1:100-2000 and then ultrasonically dispersing the mixture to obtain a nano-SiO2 dilution solution; S3. The magnesium alloy sample after electrolytic polishing in step S1 is placed in the SiO2 diluted solution treated in step S2 for ultrasonic treatment. Then the magnesium alloy sample is taken out, cleaned with alcohol and blown dry to form uniformly dispersed speckle particles on the surface of the magnesium alloy sample. The particle size of the speckle SiO2 is 20-60 nm.

2. The method for preparing μ-DIC speckle of magnesium alloy according to claim 1, characterized in that: Step S1 is specifically as follows: the magnesium alloy sample is polished from coarse to fine on 600#, 800#, 1000#, 1600#, 2000#, and 3000# sandpaper in sequence until the surface is in a mirror state, and then the magnesium alloy sample is electropolished using ACII electrolyte. The electropolishing voltage is 20V, the polishing temperature is -15~-30℃, the current density is controlled at 30~60mA, and the polishing time is 60~150s to obtain a magnesium alloy sample with a smooth surface and no stress.

3. The method for preparing μ-DIC speckle of magnesium alloy according to claim 1, characterized in that: In step S2, an ultrasonic cleaning machine is used to ultrasonically disperse the diluted solution, the ultrasonic power is 50-150W, the ultrasonic time is 30-80min, and the ultrasonic temperature is 20-50°C.

4. The method for preparing μ-DIC speckle of magnesium alloy according to claim 1, characterized in that: In step S3, the ultrasonic power is 50-150 W, the ultrasonic time is 5-30 min, and the ultrasonic temperature is 20-50° C.

5. A method for characterizing local strain in micro-regions on the surface of a magnesium alloy, characterized in that: The following steps are involved: S1. Prepare speckles on the surface of a magnesium alloy sample using the method for preparing μ-DIC speckles on a magnesium alloy as described in any one of claims 1 to 4; S2, photographing the magnesium alloy sample with speckles prepared in step S1 by using a secondary electron imaging mode of a scanning electron microscope to obtain an undeformed SEM image, and photographing the region by using a backscattered electron diffraction mode to obtain an undeformed EBSD image of the region; S3, performing a deformation operation on the magnesium alloy sample, photographing the deformed magnesium alloy sample through a secondary electron imaging mode of a scanning electron microscope after the magnesium alloy sample is deformed to obtain a SEM image after deformation, and photographing the region in a backscattered electron diffraction mode to obtain an EBSD image of the region after deformation; S4. Compare and analyze the undeformed SEM image in step S2 and the deformed SEM image in step S3 using computer software to obtain displacement and local strain information, and characterize the local strain of the magnesium alloy sample.

6. The method for characterizing local strain in micro-regions on the surface of a magnesium alloy according to claim 5, characterized in that: The deformation in step S3 includes bending, stretching or compression.

7. The method for characterizing local strain in micro-regions on the surface of a magnesium alloy according to claim 6, characterized in that: Step S4 is specifically as follows: using EBSD data to obtain a grain boundary distribution map of the magnesium alloy sample material, and then obtaining the local strain distribution of the magnesium alloy sample based on the speckles on the undeformed SEM image and the deformed SEM image; overlapping the grain boundary distribution map with the local strain distribution to obtain a cloud map containing both grain boundary information and strain distribution.

8. Application of the method for characterizing local strain in micro-regions on the surface of magnesium alloy as claimed in claim 5, characterized in that: This characterization method is used to evaluate the plastic deformation mechanism and damage failure of magnesium alloys, optimize the processing technology of magnesium alloys, and predict the service life of magnesium alloys.

Citation Information

Patent Citations

  • Method for quickly preparing titanium and titanium alloy EBSD (Electron Back-Scattered Diffraction) test sample under room temperature

    CN109297998A

  • Preparation method of speckle and characterization method for material microdomain deformation

    CN109580677A

  • SEM-DIC speckle preparation method for characterizing local strain distribution characteristics of material

    CN111610210A

  • Test method based on scanning electron microscope quasi-in-situ stretching EBSD and DIC signal synchronous acquisition

    CN112903393A

  • Multi-scale micro-nano speckle preparation method for SEM-DIC strain field analysis

    CN118275478A

Cited By

  • Full-automatic tensile testing machine for sheet metal and testing method

    CN120253469A